1999
DOI: 10.1109/18.796383
|View full text |Cite
|
Sign up to set email alerts
|

Multihypothesis sequential probability ratio tests .I. Asymptotic optimality

Abstract: The problem of sequential testing of multiple hypotheses is considered, and two candidate sequential test procedures are studied. Both tests are multihypothesis versions of the binary sequential probability ratio test (SPRT), and are referred to as MSPRT's. The first test is motivated by Bayesian optimality arguments, while the second corresponds to a generalized likelihood ratio test. It is shown that both MSPRT's are asymptotically optimal relative not only to the expected sample size but also to any positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
244
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(246 citation statements)
references
References 27 publications
0
244
0
2
Order By: Relevance
“…In the model there is only ever one positive RDV at a time, which represents the difference in evidence between the items with the most and next-most evidence. Therefore, the model falls into the class of "best vs. next" models that are known to implement the asymptotically optimal MSPRT in the absence of attention biases (5,33,35). We emphasize, however, that once visual attention biases are present, neither the two-item version of the DDM, nor the multi-item version presented here, is optimal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the model there is only ever one positive RDV at a time, which represents the difference in evidence between the items with the most and next-most evidence. Therefore, the model falls into the class of "best vs. next" models that are known to implement the asymptotically optimal MSPRT in the absence of attention biases (5,33,35). We emphasize, however, that once visual attention biases are present, neither the two-item version of the DDM, nor the multi-item version presented here, is optimal.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the optimal statistical test associated with the case of multiple alternatives is unknown, and only approximations have been proposed (32,33). Out of the alternatives that have been proposed, the multihypothesis sequential probability ratio test (MSPRT) is a particularly appealing one, because it reduces to the SPRT in the case of two options, and is asymptotically optimal in the sense that for sufficiently low error rates it minimizes expected decision time (5,25,33,35).Second, the classic DDM and leaky integrator models have ignored the role that visual attention plays in the choice process. This gap is an important limitation because both casual observation and previous research suggest that visual fixations play a role in the decision-making process (18,36,37).…”
mentioning
confidence: 99%
“…Both change detection and sequential multi-hypothesis testing have been studied extensively. For recent reviews of these areas, we refer the reader to Basseville and Nikiforov [3], Dragalin, Tartakovsky and Veeravalli [8,9], and Lai [14], and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…The non-Bayes formulation of the sequential hypothesis testing problem has been studied by many authors, both in discrete-and continuous-time, and can be found in the recent reviews and contributions made by Lai (2000Lai ( , 2001, Dragalin et al (1999Dragalin et al ( , 2000, Lorden (1977). In the Bayesian framework, sequential hypothesis testing problems were studied in discrete-time for the identification of the distribution of i.i.d.…”
Section: Introductionmentioning
confidence: 99%